TATA KELOLA MASJID AGUNG ISLAMIC CENTRE KABUPATEN ROKAN HULU - Sonia (Prodi Pengembangan Masyarakat Islam STAI Diniyah Pekanbaru, 2025)
Abstrak Tujuan penelitian ini adalah untuk mengetahui Tata Kelola Masjid Agung Islamic Centre Kabupaten Rokan Hulu yang telah dilakukan oleh Badan Pengelola Masjid Agung Islamic Centre Kabupaten. Adapun jenis penelitian yang digunakan pada penelitian ini adalah penelitian kualitatif dengan teknik pengumpulan data secara observasi, wawancara dan dokumentasi. Dari hasil analisis masing-masing indikator pengukur keberhasilan tata kelola,berupa indikator Partisipas, Transparansi, Akuntabilitas, Efektifitas, Kepastian hukum, Responsif maka hasil yang diperoleh dari penelitian ini menunjukan bahwa tata kelola masjid agung Islamic centre Kabupaten Rokan Hulu dapat dikatakan sudah terlaksana tetapi belum terwujud secara ideal sehingga pelaksanaan tata kelola masjid agung Islamic centre ini belum berlangsung optimal. Faktor penghambat dalam tata kelola masjid agung Islamic centre ini adalah kurangnya sumber daya manusia yang tidak maksimalnya kinerja dan belum sesuai dengan kompetensinya, serta rendahnya tingkat koordinasi antar badan pengelola. Kata kunci: Tata Kelola, Masjid Agung Islamic Centre Kabupaten Rokan Abstract The purpose of this study was to determine the Governance of the Great Mosque of the Islamic Center of Rokan Hulu Regency which has been carried out by the Management Board of the Great Mosque of the Islamic Center of the Regency. The type of research used in this study is qualitative research with data collection techniques through observation, interviews and documentation. From the results of the analysis of each indicator measuring the success of governance, in the form of indicators of Participation, Transparency, Accountability, Effectiveness, Legal Certainty, Responsiveness, the results obtained from this study indicate that the governance of the Great Mosque of the Islamic Center of Rokan Hulu Regency can be said to be good but has not been realized ideally so that the implementation of the governance of the Great Mosque of the Islamic Center has not been optimal. The inhibiting factors in the governance of the Great Mosque of the Islamic Center are the lack of human resources whose performance is not optimal and is not in accordance with their competence, as well as the low level of coordination between the management bodies. Keywords: Governance, Islamic Center Grand Mosque, Rokan Regency